AGENCIFICATION OF PUBLIC ADMINISTRATION IN THE TRANSITION PROCESS - Milica Škorić (University Business Academy in Novi Sad Faculty of Law for Commerce and Judiciary, 2021)
The democratization of the countries in Central and Eastern Europe (CEE) has also included the reform of inefficient public administration. At the same time, these reforms have been accompanied by the aspiration for a membership in the European Union. The administration has been transformed according to a number of principles that make up the framework of the European administrative area. Along with these processes, there were established public agencies, a body taken over from the developed countries, and created during the reform of the New Public Management. The countries in transition have gone through an extensive and rapid process of agency. Due to a high level of autonomy after the formation of agencies, i.e., after certain tasks have been transferred to their competence, it is difficult to eﬀectively control their work. The public interest is threatened by the non –transparency of these bodies. Their existence also aﬀects the basic principles of the European administrative space and turns the reform against itself. It is certain that the mass establishment of a new body in the system of public administration brings uncertainty in terms of eﬀects. It has turned out that foreign experts, without knowledge of the administrative tradition of the socialist countries, as well as domestic politicians who wanted accelerated reform, also contributed to that.